Simulations of a new electron gun for the TITAN EBIT. Issue 1 (1st April 2022) - Cardona, J D; Dietrich, K; Mukul, I; Dilling, J; Gwinner, G; Kester, O; Kwiatkowski, A A
Abstract: Penning trap mass spectrometry is the tool of choice for mass measurements to test the Standard Model or lay the nuclear-physics foundation of neutrino physics due to the high precisions achievable. This precision can be further boosted by higher charge states (Ettenauer et al 2011). For this purpose, an electron beam ion trap (EBIT) provides radioactive HCIs at the TITAN facility at TRIUMF. To improve the electron beam properties and its control, a new electron gun is under development. The electron gun within its TITAN EBIT environment was simulated using Field Precision's TRAK software. A new electrode geometry was chosen and optimized to extract up to 5A, 66 keV electron beams. Due to the strong fringe field of the unshielded 6T magnet, options for the passive and active shielding of the gun were explored to compress the electron beam. During the design process, careful attention was paid to safety and mechanical considerations. Simulations and the status of the new electron gun will be presented.